Determinants affecting employees’ satisfaction in ELID Sdn Bhd / Nur Sari Syakirin Mohd Amran - Mohd Amran, Nur Sari Syakirin (Faculty of Business and Management, 2012)
In this new era of globalisation, job satisfaction plays important element in any organization. We can say that job satisfaction is the starting point in order to make sure the organization really success in their business. But, this key point always been unrealized by the organization because they are too busy thinking on how to create more money and benefit day by day. The organization may achieve their target in business, but they will face lots of problem if their workers feel unsatisfied with their job. As a result, the employees will create a problem on productivity, absenteeism, turnover rates, as well as disciplinary problem. ELID Sdn Bhd has about 95 employees and of course will face the same problem if management does not even bother to take care on factor that leads to employees’ job satisfaction. Due to these reasons, the researcher decided to do research on this topic to gain in depth understanding on determinants affecting employees’ satisfaction thus able to make them stay loyal in a company.